2017
DOI: 10.1080/01480545.2017.1415926
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of aspirin against mitomycin C-induced carcinogenicity, assessed by the test for detection of epithelial tumor clones (warts) in Drosophila melanogaster

Abstract: The present study assessed the protective effect of aspirin against carcinogenicity induced by mitomycin C (MMC) by the test for detection of warts/epithelial tumor clones in Drosophila melanogaster. Larvae were treated with different concentrations of aspirin alone (10, 20 or 40 mg/mL) or aspirin in association with MMC. MMC and ultrapure water were employed as the positive and negative control, respectively. Antioxidant activity was determined using the DPPH method. For performing cytotoxicity assay on HeLa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Сделанные выводы, согласуются с результатами, полученными в 2018 г., в работе группы бразильских учёных, которые также занимались изучением протекторных свойств аспирина [10]. В результате проведённых исследований ими были выявлены антиоксидантные свойства ацетилсалициловой кислоты.…”
Section: Discussionunclassified
“…Сделанные выводы, согласуются с результатами, полученными в 2018 г., в работе группы бразильских учёных, которые также занимались изучением протекторных свойств аспирина [10]. В результате проведённых исследований ими были выявлены антиоксидантные свойства ацетилсалициловой кислоты.…”
Section: Discussionunclassified
“…96,97 Compared to CCDF and other specimens, commercially available synthetic anticoagulants heparin and aspirin exhibited lower antioxidant potential. Oliveira et al 98 reported that aspirin demonstrated less than 20% antioxidant activity as measured by the DPPH radical scavenging capacity assay. In contrast, CCDF specimen demonstrated more than 70% antioxidative potential.…”
Section: (D)mentioning
confidence: 99%